Peran Tokoh Agama dalam Menanggulangi Dampak Negatif dari Perkebunan Kelapa Sawit di Nagari Ranah Koto Tinggi Kecamatan Koto Balingka Kabupaten Pasaman Barat - Riska Yuni; Noor Fadlli Marh (Lembaga Yasin AlSys, 2026)
Although the negative impacts of oil palm plantation development on the economic and social lives of communities and community development have been widely studied, research specifically analyzing the role of religious leaders in addressing the resulting social impacts remains limited. This study aimed to analyze the role of religious leaders in addressing the negative impacts of oil palm plantation development in Ranah Koto Tinggi Village, Koto Balingka Subdistrict, West Pasaman Regency. This study employed a qualitative approach with a descriptive design through field research, involving 12 informants selected using purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data reduction, data display, and conclusion drawing. The results showed that religious leaders performed two main roles, namely as religious leaders and community members. These roles were manifested through religious guidance, family assistance, youth development, religious consultation, and persuasive approaches to entertainment venue owners (pakter). Although various efforts had been undertaken, their effectiveness remained suboptimal because of economic and social factors that allowed deviant practices to persist. These findings reinforce the relevance of Erving Goffman’s Dramaturgical Theory in explaining the function of religious leaders as agents of social control amid social changes resulting from oil palm plantation development. This study contributes to the development of the sociology of religion and emphasizes the importance of synergy among religious leaders, the village government, ninik mamak, and the community in formulating more comprehensive prevention strategies to address the negative social impacts of oil palm plantation development.